Production, purification and physicochemical characterization of D-xylose/glucose isomerase from Escherichia coli strain BL21 - Fatima, Bilqees (3 Biotech, 2020)
Cell lysate of Escherichia coli strain BL21 showed significant D-glucose isomerase activity. The rate of glucose conversion was increased up to 40% when cells were induced with 1% D-xylose. E. coli BL21 xylose isomerase (ECXI-BL21) was purified to homogeneity, up to 1.9-fold with overall 10.88% enzyme yield by heat shock, salting out and electro-elution. The molecular mass of ECXI-BL21 was estimated as 43.9 kDa on SDS-PAGE. pH(opt.) and T(opt.) of the enzyme were calculated as 7.0 and 50 °C, respectively. Activation energy (E(a)) of ECXI-BL21 was 45 kJ/mol. Enzyme was stable from 30 to 55 °C and at pH range 6.0–8.0. ECXI-BL21((holo)) was activated by 10 mM magnesium (35%), 0.5 mM cobalt (20%) and manganese (25%), and 0.5/10 mM Mn(2+)/Mg(2+) (50%) and Co(2+)/Mg(2+) (30%) as compared to ECXI-BL21((apo)). Catalytic affinity (K(m)) of ECXI-BL21 for D-glucose was calculated as 0.82 mM, while maximum velocity (V(max)) of the reaction D-glucose((aldo)) ⇌ D-fructose((keto)) was 108 μmol/mg/min. D-fructose formed was identified on silica gel plate. This thermophilic enzyme, T(m) = 75 °C, has great potential for high fructose syrup production used in food and soft drink industries.